The philosophy of management - Sheldon, Oliver (Early sociology of management and organizations, 2003)
Sheldon's work prefigures the human relations approach to management theory of Elton Mayo and F.J. Roethlisberger in rejecting the notion that economic incentives largely explain employee behaviour.